PEMEKARAN KECAMATAN DI KABUPATEN AGAM : LAHIRNYA KECAMATAN MALALAK 2003-2012 - Prawati, Riri; Husnita, Liza; Yulia, Refni (Pendidikan Sejarah, 2014)
ABSTRACTThis thesis examines the developing area districts in Agam: Birth of the District Malalak ( 2003-2012 ). To facilitate this research, the problem can be formulated as follows: (1) How is the formation of the District Redistricting Malalak. (2) how the impact of the District Redistricting Malalak Malalak on peoples lives, especially in terms of the socio-cultural, political, economic, education and health. The purpose of this study is (1) To explain the process of the formation of the District Redistricting Malalak. (2) To explain the effect of splitting the District Malalak Malalak on peoples lives, especially in terms of the socio-cultural, political, educational, economic, and health. The method used in this study is the historical method . The method consists of the following four stages: (1) Heuristic is a collection of data, looking for the source and conclude that the way indent literature study and interviews. Stage (2) Criticism source, in order to obtain the facts of history. Stage (2) Interpretation of the data obtained is then analyzed and interpreted by means of connecting and comparing the observed facts so that there is ready fakata presented. Stage (4) Historiography is writing in the form of scientific papers after it was found the data and facts that really accurate and valid then written in the form of a thesis. The results of this study describes: (1)The process of forming the District Redistricting Malalak Agam is starting Redistricting Malalak Nagari Nagari is divided into four, namely Malalak Nagari West, North Malalak Nagari, Nagari Nagari Malalak Malalak East and South to the District Malalak definitive proposal. (2) The effects of Redistricting District of Malalak on peoples lives Malalak of Social Affairs is the creation of a sense of brotherhood among the Minang People with other tribes in the District Malalak such as Sundanese, Javanese and Batak. The impact in the field of politics that is the community participation Malalak dabbling in politics, the health sector has been the availability of health facilities such as health centers, sub health centers, integrated health, along with health professionals, and the community economically Malalak already quite improved.